Taxanes induced hypersensitivity reactions in cancer chemotherapy patients reported at adverse drug reaction monitoring centre at a tertiary care hospital - Begum, Shaik Haseena; M., Venugopal Reddy; Sahayaraj, Christina; S., Sharon Sonia; Y., Vijayabhaskara Reddy (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Cancer chemotherapy involves highly complex regimens using antineoplastic agents like taxanes (paclitaxel, docetaxel) etc. Taxanes cause hypersensitivity reactions (HSRs) like redness, rashes, dyspnoea, severe anaphylaxis and death. In this study, adverse drug reactions (ADRs) associated with taxanes are described & analysed on their severity and preventability. The present study aims to analyse and determine the prevalence of ADRs, especially HSRs in patients treated with taxanes. Methods: After getting IEC approval, the present study is done retrospectively by assessing the HSRs in suspected ADR reporting forms from December 2019 to February 2022 in ADR monitoring centre (AMC) in the Department of Pharmacology at Kurnool Medical College, Kurnool. Descriptive statistics used to analyse patient demography, frequency, various carcinomas under treatment & organ involved, causality assessment using WHO-UMC Scale and Naranjo’s Algorithm, severity assessment using modified Hartwig & Siegel’s scale and preventability by modified Schumock & Thornton scale. Results: A total of 258 ADRs were recorded, of which 30 cases reported HSRs with taxanes-paclitaxel (22) and docetaxel (8). The most commonly occurred HSR is shortness of breath. Naranjo’s algorithm showed 52.5% possible (score 1-4) HSRs. WHO-UMC causality assessment scale showed 56.4% as probable HSRs. Modified Hartwig & Siegel severity scale showed 46.6% moderate (level 3). Modified Schumock and Thornton scale showed 76.9% as not preventable. Conclusions: Chemotherapy-related ADRs among cancer patients urges the oncologists to be actively involved in ADR reporting, in the need of the hour in order to mitigate, avoid their occurrence and reducing morbidity and mortality, when practiced with diligence.